Legitime Portie dalam Pemberian Hibah Wasiat - Nurul Aqidatul Izzah; Saharuddin Saharuddin; Bakhtiar Tijjang (Jurnal Litigasi Amsir, 2022)
This study aims to determine the provisions in the Civil Code regarding the granting of wills that violate the legitime portie. And to find out the legal consequences of granting a will that violates the legitime portie. This research uses normative research with a statutory approach, and sources of legal materials use primary legal materials, secondary legal materials and tertiary legal materials. The results of the study indicate that the provisions regarding the provision of will grants in the Civil Code that the distribution of inheritance or grants are given to lower heirs or upper heirs as stipulated in the law and do not violate the absolute part (legitime portie) that has been regulated in the Civil Code. The legal consequences that occur when the granting of a will violates the legitime portie, namely an incorting and also the implementation of a testamentary grant. Incorting is carried out by prosecution by the heirs. Meanwhile, if the legitimate heir does not file an objection, then the act of grant that violates the absolute part (legitime portie) is considered still valid and carried out.